Knockdown of enhancer of rudimentary homolog expression attenuates proliferation, cell cycle and apoptosis of melanoma cells. Issue 4 (August 2021) - Xiao, Muzhang; Tang, Ningning; Yan, Yu; Li, Zhelin; Shi, Shupeng; He, Siqi; Chen, Zizi; Cao, Ke; Chen, Jia; Zhou, Jianda; Chen, Xiang
Abstract : Early stage or localized melanoma can be surgically resected with satisfactory outcome, whereas advanced malignant melanoma responds to treatment poorly and has a negative prognosis even after surgery, radiotherapy and other comprehensive treatments. Gene therapy targeting various biological signaling pathways has become an increasingly popular area in melanoma research. However, for gene therapy success, it is important to reveal the molecular mechanisms of melanoma tumorigenesis and development. The present study examined the effects of downregulating enhancer of rudimentary homolog (ERH) expression on the proliferation, metastasis and cell cycle of melanoma cells. ERH expression levels in melanoma tissues and cells were determined. Then, ERH gene expression in melanoma cell lines was downregulated or overexpressed by the lentiviral RNA interference technique. Furthermore, we performed cell counting kit-8, clone formation, scratch, transwell migration, subcutaneous tumorigenesis and venous metastasis assays as well as carried out flow cytometry analysis to explore the effects of ERH expression on cell proliferation, cell cycle, apoptosis and metastasis. We found that ERH expression in melanoma tissues and cells was markedly higher than in normal melanin nevus. Suppressing ERH expression by RNA interference in melanoma A375, WM35 and SK28 cell lines inhibited their proliferation and induced cell apoptosis. The cell cycle was also found to be blocked in the G1 phase. However, the metastatic properties of melanoma cells in vitro and in vivo remained largely unaltered by ERH knockdown. Our results show that ERH expression is increased in melanoma. Meanwhile, the proliferation and cell cycle transformation abilities are impaired potentially by downregulating the ERH expression in melanoma cells. Therefore, targeting ERH might serve as a novel therapeutic approach for malignant melanoma.